2017
DOI: 10.1002/biot.201700169
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Vascularized Device for Subcutaneous Transplantation of Human Islets

Abstract: Transplantation of pancreatic islets or stem cell derived insulin secreting cells is an attractive treatment strategy for diabetes. However, islet transplantation is associated with several challenges including function-loss associated with dispersion and limited vascularization as well as the need for continuous immunosuppression. To overcome these limitations, here we present a novel 3D printed and functionalized encapsulation system for subcutaneous engraftment of islets or islet like cells. The devices wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 29 publications
2
70
0
1
Order By: Relevance
“…For example, we might consider increasing hsRL production by transduced cells, by using a higher MOI; using telomerase overexpression in LVhsRL‐transduced Rankl −/− MSCs to augment their proliferation ; implanting a higher number of scaffolds or larger scaffolds (as far as this is technically feasible in these small mice); using a biomimetic smart scaffold functionalized to enhance MSC attachment ; isolating the system from the host cells by means of newly developed cell encapsulation systems, thus preventing its disruption . The optimization of these aspects might be pursued, for example, by exploiting the emerging technology of rechargeable devices containing 3D printed cell‐seeded functionalized scaffolds , which has already achieved promising results in other fields. Thus, the integration of the strengths of our strategy with these new tools will likely achieve a net improvement.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we might consider increasing hsRL production by transduced cells, by using a higher MOI; using telomerase overexpression in LVhsRL‐transduced Rankl −/− MSCs to augment their proliferation ; implanting a higher number of scaffolds or larger scaffolds (as far as this is technically feasible in these small mice); using a biomimetic smart scaffold functionalized to enhance MSC attachment ; isolating the system from the host cells by means of newly developed cell encapsulation systems, thus preventing its disruption . The optimization of these aspects might be pursued, for example, by exploiting the emerging technology of rechargeable devices containing 3D printed cell‐seeded functionalized scaffolds , which has already achieved promising results in other fields. Thus, the integration of the strengths of our strategy with these new tools will likely achieve a net improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate oxygen supply causes the gradual loss of cell mass and function, and this effect can be aggravated with encapsulation, thus pose one of the challenges in BAP development . To overcome this problem, several different experimental approaches have been tested such as the stimulation of vascularization growth prior to cell transplantation, the use of a hypoxia‐resistant cell line from Tilapia, microencapsulation, increased oxygen permeability of the encapsulating material . Incorporated refillable oxygen reservoir in the βAir device has already been tested in small and large animal models, and recently, in a clinical phase I study (Clinicaltrials.gov: NCT02064309) has been conducted to evaluate its safety .…”
Section: In Vivo Studies In Pigs—the Bioartificial Pancreas (Bap)mentioning
confidence: 99%
“…Most of these studies have reported an improvement in islet engraftment and a decreased immune response. Furthermore, insulinotropic peptides, such as glucagon‐like peptide‐1 (GLP‐1), exendin‐4 (Ex‐4), or insulin‐like growth factor‐1 (IGF‐1), as well as proangiogenic factors and cells such as VEGF, platelet‐derived growth factor (PDGF), and endothelial cells (ECs), have been combined with these scaffolds and islets, in both in vitro (Kizilel et al, ; Lin & Anseth, ) and in vivo approaches (Brady et al, ; Farina et al, ; Hlavaty et al, ; Y. Li et al, ; Linn et al, ; Phelps, Headen, Taylor, Thulé, & García, ; Phelps, Templeman, Thulé & García, ), showing significant improvements in insulin secretion, islet survival, and engraftment. In other studies, immunosuppressive drugs (Haque, Jeong, & Byun, ; Pinto et al, ) or even immunomodulatory cells, such as regulatory T cells (Treg; Graham et al, ) or mesenchymal stem cells (MSCs; Borg et al, ; Gołąb et al, ; Marek et al, ), were combined with synthetic materials and used in vitro and in vivo to enhance their immunoprotective functions and subsequently prevent the immune reaction against nonautologous islets.…”
Section: Tissue Engineering In Islet Transplantationmentioning
confidence: 99%
“…Some strategies have been used to overcome these limitations, including encapsulation, scaffolds, accessory cells, and/or trophic factors such as fibroblast growth factor (aFGF and bFGF) or vascular endothelial growth factor (VEGF) plus hepatocyte growth factor (HGF; Golocheikine et al, 2010;Kawakami et al, 2000;Kawakami et al, 2001;Sakata et al, 2014;Smink et al, 2017). In the last year, a few studies of subcutaneous islet transplantation have been published, highlighting the great interest of the scientific community in using this anatomical site (Bertuzzi & De Carlis, 2018;Farina et al, 2017;Hsu, Fu, & Wang, 2017;Komatsu et al, 2017;Pathak et al, 2017;Pepper et al, 2017;Perez-Basterrechea et al, 2017;Uematsu et al, 2018;Vlahos, Cober, & Sefton, 2017). However, there have been few attempts to apply this approach in humans.…”
Section: (D)mentioning
confidence: 99%